2013
DOI: 10.1002/hep.26403
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation-Induced Hepatocellular Carcinoma Is Dependent on Ccr5 in Mice

Abstract: Human hepatocellular carcinoma (HCC) is an inflammation-induced cancer, which is the third-leading cause of cancer mortality worldwide. We investigated the role of the chemokine receptors, CCR5 and CCR1, in regulating inflammation and tumorigenesis in an inflammation-induced HCC model in mice. Multidrug resistance 2 gene (Mdr2)-knockout (Mdr2-KO) mice spontaneously develop chronic cholestatic hepatitis and fibrosis that is eventually followed by HCC. We generated two new strains from the Mdr2-KO mouse, the Mdr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(51 citation statements)
references
References 34 publications
1
47
0
3
Order By: Relevance
“…Accumulated evidence indicates that the progression of PLC is correlated closely with both inflammation[10] and immunocytes [11]. Recent studies suggest a potential prognostic role of the NLR in the treatment strategies of PLC, including hepatic resection,[12], [13], [14] liver transplantation,[15], [16], [17] radiofrequency ablation (RFA),[18], [19] and trans-arterial chemo-embolization (TACE)[20], [21].…”
Section: Introductionmentioning
confidence: 99%
“…Accumulated evidence indicates that the progression of PLC is correlated closely with both inflammation[10] and immunocytes [11]. Recent studies suggest a potential prognostic role of the NLR in the treatment strategies of PLC, including hepatic resection,[12], [13], [14] liver transplantation,[15], [16], [17] radiofrequency ablation (RFA),[18], [19] and trans-arterial chemo-embolization (TACE)[20], [21].…”
Section: Introductionmentioning
confidence: 99%
“…On the one hand this process seems dependent on a protein which is on the surface of white blood cells, the C-C chemokine receptor type 5 (CCR5 or CD195) [132], while on the other hand, it is dependent on TGF-β induced Smad phospho-isoform signaling [131]. Neutrophil granulocytes significantly influence the concentration gradient of chemokines such as the cytokine chemokine (C-X-C motif) ligand 1 (CXCL1).…”
Section: In Vitro and In Vivo Evidencementioning
confidence: 99%
“…Using multidrug resistance 2 gene (Mdr2)-knockout (Mdr2-KO) mice developing HCCs in inflamed livers, the authors demonstrated that CCR5 seems to be more prominently involved in several pathways of tumor development, including both the inflammatory responses that induce oncogenic stress and the recruitment of macrophages that facilitates progression and maintenance of HCCs, than CCR1 [22]. However, with respect to CCR1, several reports were recently published demonstrating that a CCR1-mediated accumulation of positive myeloid cells in the liver microenvironment promotes liver metastasis development in mice, indicating that the therapeutic targeting of CCR1 could significantly contribute to the establishment of novel therapy options for patients suffering from liver metastasis [23,24,74,75].…”
Section: Ccl5-ccr1/5 Axismentioning
confidence: 98%
“…Based on the fact that CCR1 and CCR5 both play a significant role in establishing a pro-inflammatory and pro-fibrotic milieu in injured livers, Barashi et al investigated the role of both chemokine receptors in regulating tumorigenesis in an inflammation-induced HCC model in mice [22]. Using multidrug resistance 2 gene (Mdr2)-knockout (Mdr2-KO) mice developing HCCs in inflamed livers, the authors demonstrated that CCR5 seems to be more prominently involved in several pathways of tumor development, including both the inflammatory responses that induce oncogenic stress and the recruitment of macrophages that facilitates progression and maintenance of HCCs, than CCR1 [22].…”
Section: Ccl5-ccr1/5 Axismentioning
confidence: 99%